Exploring the Impact of Gender on Student Access to and Utilization of Educational Technology in South African Higher Education: A Systematic Review on Equity and Inclusion - Matobobo, Ophellia; Matobobo, Courage (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study explored the impact of gender on student access to and utilization of educational technologies in South African higher education, with a focus on how these dynamics affect equity and inclusion. Using a systematic review approach, sixteen peer-reviewed studies were analysed thematically to uncover patterns of gendered disparities across technological platforms, learning contexts, and student demographics. The findings reveal that female students, particularly those from rural, low-income, or marginalised backgrounds, face significant structural barriers to accessing devices, connectivity, and digital learning spaces. Gendered social roles and responsibilities also shape how technology is used, with women often engaging more passively and asynchronously due to caregiving duties and domestic constraints, while men dominate synchronous and institutional platforms. Intersectional disadvantages, especially among incarcerated women and those with disabilities, further compound digital exclusion. Although female students frequently demonstrate strong academic outcomes when provided equitable access, institutional policies and support systems remain inadequately gender-responsive. The study concludes that meaningful inclusion in digital higher education requires not only access but also the freedom and institutional support to engage equitably. The paper calls for gender-sensitive policy reform, inclusive EdTech design, and targeted interventions that dismantle systemic barriers to digital participation in higher education.